Recovering Voiding and Sex Function in a Patient with Chronic Complete Spinal Cord Injury by Olfactory Ensheathing Cell Transplantation - Di Chen; Haitao Xi; Ke Tan; Hongyun Huang (Case Reports in Neurological Medicine)
Spinal cord injury (SCI) is life-altering damage for patients, their family, and society. Transplantation of olfactory ensheathing cells has demonstrated neurorestoration effects for many neurological conditions, including SCI. But voiding and sex dysfunction in patients with chronic complete SCI is still a major issue even though neurorestorative therapies can restore their partial neurological functions. Here we report a case with traumatic complete SCI at the level of C6-C7 one year ago, who received OEC transplantation with intensive neurorehabilitation. The patient started to show clinical improvements within a few days after cell treatment. Six-year follow-up demonstrated his American Spinal Injury Association (ASIA)-Impairment Scale change from ASIA A to become ASIA C. The scores of International Association of Neurorestoratology Spinal Cord Injury Functional Rating Scale changed from 14 (prior to cell therapy) to 31 + 3 (six years after cell therapy). His main improvements in activity of daily life included eating, dressing and writing by himself, standing and walking, and urine control or voiding. His sex function recovered to be normal. He married and had a son through natural sex life. His improving functions and activities of daily life stayed stable in subsequent phone call follow-up. This was one individual case report. In the future, the deep mechanisms of why he got positive results, but other patients with similar condition did not get so much benefits from OEC transplantation should be explored.